Johnson & Johnson Asia Pacific Supply Chain: A Value(less) Chain? - Wong, Wennie (2008)
An increasing number of companies claim to pursue International supply chain management (ISCM), but the empirical evidence of successful implementation programs is still scarce. This project aims to contribute in this area by presenting an review of goals, barriers, and enablers on the road towards effective ISCM by Johnson and Johnson Asia Pacific. In today's highly competitive globalized environment, organizations must seek to develop collaborative partnerships and more effective information links with trading partners; it is inevitable that internal processes must become interlinked and span beyond the traditional boundaries of firms. Physical logistics have become more dependent on information technologies, and these technologies are critical enablers of further cooperative arrangements towards ISCM. The management of an extended enterprise as a network of processes, relationships and technologies creating an interdependence and shared destiny is now a prerequisite for a successful international supply chain. The truly strategic nature of international supply chain management thus becomes apparent for companies seeking to compete effectively, with successful implementation becoming a source of competitive advantage.